Building school and community collaboration in realizing competitive vocational high school graduates - Suhari Muharam; Raden Bambang Sumarsono; Agus Timan (Universitas Papua, 2026)
Enhancing the competitiveness of vocational school graduates requires strong collaboration between schools and society as an integrated educational ecosystem. This collaboration extends beyond partnerships with businesses and industries to include the active involvement of parents, institutions, and local communities in supporting student development. The school's public relations function plays a strategic role in fostering communication and cooperation between schools and their stakeholders. This study aims to analyze the role of public relations in fostering collaboration between schools and communities to produce competitive vocational graduates. It also identifies internal and external challenges and the strategies developed to address them. Using a qualitative approach with a case study design at one of the SMK Mutu in Malang, data were collected through in-depth interviews, observations, and document analysis. These data were then processed using NVivo 14 for coding and thematic identification. The results reveal that public relations serves as a central coordinator for cross-sector collaboration and as an adaptive agent, employing problem-solving and collaborative strategies to address school challenges. These findings underscore that public relations acts as a key mediator, ensuring the effective and sustainable operation of school-community partnerships to enhance the quality and competitiveness of vocational education.